Community-based development of suli tourism village, salahutu district, Central Maluku Regency, Maluku Province - Hellen Sarita De Lima; Francisca Titing Koerniawaty; I Made Darsana (Jurnal Mantik, 2023)
Suli Village is located in Subdistrict of Salahutu, which is rich of its Nature, Culture, Culinary and History. The area is divided into 4 (four) villages namely, Amalatuei village, Latuslamu village, Wainusalaut village and Amarumatena village. This division has both direct and indirect influence toward the management of tourism attractions in the area. Suli Village has been designated as Tourism Village since 2021 by the Regent of Central Maluku Regency, however, there was no coordination neither with Suli Village nor with the village community. Even though the people of Suli Village really wanted to be involved. Tourist attractions aside from Natsepa Beach, have not been determined as tourist destination. This research aims to identify opportunities, challenges and threats that may affect the sustainability of tourism attractions and environment in Suli Village, as well as observing the role of government, people's character and capabilities to be contributed to supporting the development of a tourist village and formulate community – based tourism village development strategies program. This research utilizes descriptive qualitative methods and analysis of development strategies using SWOT (IFAS EFAS) which produces 4 (four) strategic aspects, namely destination aspects, management aspects, institutional aspects and marketing aspects.The results of the study showed that the Central Maluku Regency Government has not played a serious role in the development of Suli Tourism Village attractiveness, as there is not any blueprint available, the facilities and infrastructures have not met the requirements of tourism standards.